Finger pad friction and tactile perception of laser treated, stamped and cold rolled micro-structured stainless steel sheet surfaces - S. Zhang; X. Zeng; D. T. A. Matthews; A. Igartua; E. Rodriguez–Vidal; J. Contreras Fortes; E. Van Der Heide (Friction)
Abstract Tactile perception is a complex system, which depends on frictional interactions between skin and counter-body. The contact mechanics of tactile friction is governed by many factors such as the state and properties of skin and counter-body. In order to discover the connection between perception and tactile friction on textured stainless steel sheets, both perception experiments (subjective) and tactile friction measurements (objective) were performed in this research. The perception experiments were carried out by using a panel test method to identify the perceived roughness, perceived stickiness and comfort level from the participants. For the friction experiments, tactile friction was measured by a multi-axis force/torque transducer in vivo. The perceived stickiness was illustrated as an effective subjective stimulus, which has a negative correlation to the comfort perception. No significant evidence was revealed to the connection between the perceived roughness and comfort perception, and this relationship may be influenced by the participants’ individual experience, gender and moisture level of skin. Furthermore, the kinetic tactile friction was concluded as an objective stimulus to the comfort perception with a negative correlation.